2011
DOI: 10.1179/136485911x12987676649421
|View full text |Cite
|
Sign up to set email alerts
|

Human malaria in the highlands of Yemen

Abstract: , a cross-sectional study of human malaria was carried out in four governorates of Yemen, two (Taiz and Hodiedah) representing the country's highlands and the others (Dhamar and Raymah) the country's coastal plains/foothills. The main aims were to determine the prevalences of Plasmodium infection among 455 febrile patients presenting for care at participating health facilities and to investigate the potential risk factors for such infection.Malarial infection was detected in 78 (17.1%) of the investigated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Males are also perceived to be more active in outdoor activities which make them more vulnerable to the bites of mosquitoes. This observation is consistent with other studies conducted in Yemen [10,8].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Males are also perceived to be more active in outdoor activities which make them more vulnerable to the bites of mosquitoes. This observation is consistent with other studies conducted in Yemen [10,8].…”
Section: Discussionsupporting
confidence: 94%
“…Later, WHO reported epidemics of dengue fever in some parts of Yemen that spread in the coastal planes of Tehama and Abyan that the dengue fever became epidemic in some parts of Yemen that spread in the coastal planes of Tehama and Abyan [9]. Also, malaria is an endemic in Hodeidah, Yemen [10].…”
Section: Introductionmentioning
confidence: 99%
“…In sharp contrast to other countries in the Arabian Peninsula, all reported cases of malaria in Yemen were attributable to local transmission [28]. Up to 69% of the population live in areas of high transmission (≥1 case/1000), with 99% of confirmed infections being attributable to P. falciparum [34]. Significantly higher infection rates are seen in the rural areas, and severe malaria accounts for up to 20% of paediatric admissions [34,35].…”
Section: Malariamentioning
confidence: 99%
“…Up to 69% of the population live in areas of high transmission (≥1 case/1000), with 99% of confirmed infections being attributable to P. falciparum [34]. Significantly higher infection rates are seen in the rural areas, and severe malaria accounts for up to 20% of paediatric admissions [34,35]. In Yemen, 4.9 deaths/100 000/year and 43 000 disability‐adjusted life‐years lost were attributed to malaria in 2004 [36].…”
Section: Malariamentioning
confidence: 99%
“…In Islamic Republic of Iran, around 66% area is free from malaria, 12% area is affected by Plasmodium vivax and 6% by Plasmodium falciparum. Al Mekhlafi, et al 9 reported the prevalence of malaria in highlands of Yemen during the period from June 2008 to March 2009 as 78 (17.1428%) out of 455 Important Note: Directorate of Malaria Control (DMC), Pakistan 13 has calculated percentage for prevalence correctly by taking the total sample of 6,500,000 (6.5 million) as denominator. But percentages for distribution by places and species are not calculated correctly as DMC has taken 374,513 positive cases of malaria as denominator here.…”
Section: Introduction Introduction 11 Backgroundmentioning
confidence: 99%